Influence of print speed and nozzle diameter on the fiber alignment in 3D printed ultra-high-performance concrete - Shahzad, Qamar; Abbas, Nadeem; Akbar, Muhammad; Sabi, Ehab; Thomas, Blessen Skariah; Arshid, Muhammad Usman (Frontiers in Materials, 2024)
The limitations in the available reinforcing methods have accompanied the increasing popularity of 3D Concrete Printing (3DCP). Incorporating steel fibers as reinforcement is a promising approach to overcome these limitations. However, the impact of the printing process on the alignment of these fibers is not well understood. Therefore, the objective of this research is to quantitatively analyze the distribution of steel fiber alignment in 3D printed concrete. To achieve this, digital image analysis was employed to assess the influence of nozzle diameter, print speed, and fiber content on fiber alignment in both mold-cast and 3D-printed samples.UHPC matrix without fiber addition and fiber reinforced UHPC composites with brass-coated steel fiber contents of 1.5% and 3% by volume fraction were printed. Furthermore, Material nozzles ranging from 10 mm to 40 mm in size were employed and printing speeds of 15, 25, 35, and 45 mm/s were adjusted. Subsequently, the study examined the implications of fiber alignment on the hardened performance of printed specimens and compared them with conventionally mold-cast samples. The findings of the study demonstrated that increasing the fiber content and using smaller diameter nozzles during the printing procedure led to significant improvements in fiber orientation along the printing direction. As a result, the mechanical performance of the printed samples showed a substantial enhancement compared to the specimens produced through mold casting, primarily due to the improved fiber alignment.